SARS-CoV-2 Polymerase Chain Reaction Positivity Rates Among Evacuees From Afghanistan After Withdrawal of the Coalition Forces - Adeel A. Butt (3697705) (2022)
Afghanistan has been a major armed conflict zone for over 2 decades. Consequently, the response to multiple infectious disease threats, including the SARS-CoV-2 pandemic, has been poor because of a lack of resources and inadequate infrastructure.1,2 In August 2021, the Western coalition forces completely withdrew from Afghanistan, which further exacerbated the shortage of critical medicines and supplies.3 Qatar was the first stop for a large proportion of evacuees en route to their final destination. We conducted a cross-sectional study to determine the rate of active SARS-CoV-2 infection among evacuees arriving in Qatar from Afghanistan. Other Information Published in: JAMA Network Open License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1001/jamanetworkopen.2022.13467